Soft Skills: Concepts, Problems, Research - N.N. Avdeeva; Y.A. Kochetova; M.V. Klimakova (Современная зарубежная психология)
The work is aimed at clarifying the concept of “soft skills”. The materials of the study of concepts, problems, and research of soft skills in a professional environment are presented. The topic of soft skills is extremely relevant, both Russian and foreign students do not exactly understand what soft skills are, which may be explained by the fact that there is currently no single approach to understanding them. The purpose of studying this problem is to review concepts, problems and research on the topic of soft skills in foreign and national scientific literature. The results obtained make it possible to say that soft skills is a broad concept, and does not include a strictly defined list of qualities or abilities. There is evidence that researchers attribute a different set of abilities to soft skills, while different abilities will be most significant for different professional fields. Separately, such abilities can be distinguished as: communication skills, leadership position, decision-making skills, responsibility, empathy, self-esteem, critical thinking, analytical thinking, emotional intelligence (often assessed as part of soft skills in foreign studies). The most effective methods for developing soft skills include: methods for early development, educational tasks related to information search and analysis, critical thinking development, self-management (including the formulation of action plans), teamwork skills, and the presence of social and humanitarian disciplines (“Philosophy” and “Sociology”), as well as specialized courses such as “Team Building” and “Time Management”. It is also emphasized that the level of soft skills development among teachers is important for fostering soft skills in students.